2009
DOI: 10.1016/j.ydbio.2009.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Rap1 maintains adhesion between cells to affect Egfr signaling and planar cell polarity in Drosophila

Abstract: The small GTPase Rap1 affects cell adhesion and cell motility in numerous developmental contexts. Loss of Rap1 in the Drosophila wing epithelium disrupts adherens junction localization, causing mutant cells to disperse, and dramatically alters epithelial cell shape. While the adhesive consequences of Rap1 inactivation have been well described in this system, the effects on cell signaling, cell fate specification, and tissue differentiation are not known. Here we demonstrate that Egfr-dependent cell types are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 100 publications
2
44
0
Order By: Relevance
“…Except for the general lack of R7 cells, only a few ommatidia appear to be missing several photoreceptor cells ( Figure 5). This latter observation is consistent with previous work reporting that elimination of Rap1 activity has partial effects on photoreceptor cell differentiation (O'Keefe et al 2009). Together, while these findings indicate that Rap1 signaling plays a role during photoreceptor cell differentiation, this role is particularly critical for setting up the R7 cell differentiation program.…”
Section: Rap1 Signaling Is Required For Rtk-dependent Cell Differentisupporting
confidence: 94%
See 2 more Smart Citations
“…Except for the general lack of R7 cells, only a few ommatidia appear to be missing several photoreceptor cells ( Figure 5). This latter observation is consistent with previous work reporting that elimination of Rap1 activity has partial effects on photoreceptor cell differentiation (O'Keefe et al 2009). Together, while these findings indicate that Rap1 signaling plays a role during photoreceptor cell differentiation, this role is particularly critical for setting up the R7 cell differentiation program.…”
Section: Rap1 Signaling Is Required For Rtk-dependent Cell Differentisupporting
confidence: 94%
“…In two of these, Rap1 is suggested to serve as a direct RAF activator, which would explain how it influences RTK-dependent MAPK signaling (Lee et al 2002;Mishra et al 2005). In contrast, a third study failed to detect such a role downstream of EGFR during eye and wing development (O'Keefe et al 2009). Instead, the authors reported that Rap1 activity is required for cadherin-based adherens junction formation and that elimination of Rap1 impedes EGFR signaling as a consequence of reduced adhesive contacts between differentiating cells.…”
Section: Rap1 Signaling Is Required For Rtk-dependent Cell Differentimentioning
confidence: 99%
See 1 more Smart Citation
“…This leaves open several interesting questions; for example, it is not presently clear how EGFR signalling can promote discrete AJ suppression and elongation. It is, however, tempting to speculate that previously described links between EGFR signalling and the expression of E-Cad (Brown et al, 2006;O'Keefe et al, 2009) or Rho1 (Brodu and Casanova, 2006) might play a role during this process. (Corrigall et al, 2007;Escudero et al, 2007;Schlichting and Dahmann, 2008).…”
Section: Research Articlementioning
confidence: 98%
“…1F). Thus, in the absence of rap gene function, photoreceptors fall out of the developing retina, which likely results from the role of Rap in regulating adherens junctions (23) through the PDZ protein Canoe (24). Indeed, canoe mutant clones show similar phenotypes with basally located photoreceptors (25).…”
Section: N17mentioning
confidence: 99%